2019
DOI: 10.1111/zph.12625
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Puumala hantavirus outbreak in Black Sea Region, Turkey

Abstract: Background Some of the hantavirus species in Euro‐Asia cause haemorrhagic fever with renal syndrome (HFRS) in humans. The first documented human hantavirus infection in Turkey was diagnosed in 2009. This report describes the dynamics of the first hantavirus outbreak that emerged in humans in the Western Black Sea Region of Turkey. Methods All the suspected cases of hantavirus infection were admitted to the Infectious Diseases and Clinical Microbiology Department at the Zonguldak Bülent Ecevit University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
3
7
0
3
Order By: Relevance
“…Our research showed that of the patients assessed, middle-aged patients were predominantly affected. Furthermore, most patients were men, and the main occupation was farming, consistent with the findings of previous reports 1 , 13 , 14 , 25 . The risk prediction model showed that cultivated land was the highest risk factor for HFRS 16 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research showed that of the patients assessed, middle-aged patients were predominantly affected. Furthermore, most patients were men, and the main occupation was farming, consistent with the findings of previous reports 1 , 13 , 14 , 25 . The risk prediction model showed that cultivated land was the highest risk factor for HFRS 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Tai’an is a prefecture-level city in Shandong Province; however, the incidence of HFRS in Tai’an differs from that of Shandong as a whole. Many studies have reported that HFRS mainly affects farmers 13 , 14 . It is not clear whether other groups are at a higher risk of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were observed between groups 1 and 2 in terms of lethargy and flank pain, but none in terms of other symptoms. Length of hospital stay of the hantavirus-positive patients in our study was similar to that in Celebi et al's study [14]. Additionally, length of stay was greater in the hantavirus-positive group than in the hantavirus-negative group.…”
Section: Discussionsupporting
confidence: 88%
“…Demographic characteristics of the hantavirus-positive patients in this study (male 95%, mean age 38.6 years) were consistent with Black Sea region outbreaks (male 87.5%, mean age 45.9 years) [14] as well as with outbreaks in other European countries [15]. Although hantavirus infection is independent of age and sex, the higher prevalence in males may perhaps be attributed to greater participation in outdoor activities.…”
Section: Discussionsupporting
confidence: 76%
“…The incubation period of HFRS is approximately 12 to 16 days; however, this can vary from 5 to 42 days. The typical initial symptoms are a sudden fever lasting 3 to 8 days, and this may by followed by conjunctival hyperemia, weakness, backache, headache, abdominal pain, anorexia, vomiting, and facial flushing [ 13 ]. Hemorrhagic symptoms appear on the third to sixth day; later symptoms may include proteinuria, hypotension, shock, and mild kidney diseases.…”
Section: Introductionmentioning
confidence: 99%